Cardiac light-chain deposition disease and hints at diagnosing: a case report. Issue 2 (30th January 2023) - Nishioka, Ryo; Yoshida, Shohei; Takamatsu, Hiroyuki; Kawano, Mitsuhiro
Abstract: Background: Light-chain deposition disease (LCDD) is a systemic disorder characterized by non-amyloidotic light-chain deposition in various organs with Bence-Jones type monoclonal gammopathy. Although known as monoclonal gammopathy of renal significance, it may involve interstitial tissue of various organs, and in rare cases, proceeds to organ failure. We present a case of cardiac LCDD in a patient initially suspected of dialysis-associated cardiomyopathy. Case summary: A 65-year-old man with end-stage renal disease requiring haemodialysis presented with fatigue, anorexia, and shortness of breath. He had a history of recurrent congestive heart failure and Bence-Jones type monoclonal gammopathy. A cardiac biopsy performed for suspected light-chain cardiac amyloidosis was negative for diagnostic Congo-red stain, however, paraffin immunofluorescence examination for light-chain suggested diagnosis of cardiac LCDD. Discussion: Cardiac LCDD may go undetected leading to heart failure due to lack of clinical awareness and insufficient pathological investigation. In heart failure cases with Bence-Jones type monoclonal gammopathy, clinicians should consider not only amyloidosis but also interstitial light-chain deposition. In addition, in patients with chronic kidney disease of unknown cause, investigation is recommended to rule out cardiac light-chain deposition disease concomitant with renal LCDD. Although LCDD is relatively rare it occasionally affects multiple organs; therefore, it would be better to describe it as a monoclonal gammopathy of clinical significance rather than one of renal significance.